PENGARUH TEKANAN STAKEHOLDER TERHADAP TRANSPARANSI LAPORAN KEBERLANJUTAN PERUSAHAAN-PERUSAHAAN DI INDONESIA - Arum Hamudiana; Tarmizi Achmad (Diponegoro Journal of Accounting, 2017)
This study aims to empirically examine the effect of stakeholder pressure on transparency of Indonesian companies’s sustainability report. As a part of CSR communication strategy, each company determines the required level of transparency, which depends on the pressure of specific stakeholders in the industry.The population of this study are firms in Indonesia which published sustainability report within the evaluation period of 2012-2015. Based on purposive sampling method, this study use 91 companies as the samples. The independent variable in this study are environmentally sensitive industry, consumer proximity industry, investor-oriented industry and employee-oriented industry which measured using dummy variables. The dependent variable "transparency" is obtained using Principal Component Analysis based on the four factors namely the frequency of reporting, the application level, the declaration level, and assurance. Test analysis using simple linear regression analysis model.The results indicate that the environmentally sensitive industry and consumers proximity industry do not have a significant effect on the transparency of sustainability reporting. Meanwhile, investor-oriented industry and employee-oriented industry have a significant impact on the transparency of sustainability reporting.